Myasthenia gravis seronegative for acetylcholine receptor antibodies. - Vincent, A; Leite, M; Farrugia, M; Jacob, S; Viegas, S; Shiraishi, H; Benveniste, O; Morgan, B; Hilton-Jones, D; Newsom-Davis, J; Beeson, D; Willcox, N (2008)
Antibodies to muscle-specific kinase (MuSK) are found in a variable proportion of patients with myasthenia without typical acetylcholine receptor (AChR) antibodies, but their characteristics and pathogenic mechanisms are not fully understood. We discuss the incidence and pathogenicity of MuSK antibodies and how clinical studies, animal models, and cultured cell lines can be used to elucidate their pathogenic mechanisms. Patients without either AChR or MuSK antibodies (seronegative myasthenia) appear to present another disease subtype that is highly similar to that of typical myasthenia gravis. We demonstrate a new method that detects AChR antibodies in these patients and show that these low-affinity AChR antibodies are predominantly IgG1 and can activate complement C3b deposition. Similarly MuSK antibodies, although mainly IgG4, are partially IgG1 and can activate C3b deposition. Overall, these results suggest that complement-activation may be an important pathogenic mechanism even in patients without conventional AChR antibodies.